1-stearoyl-2-arachidonoyl-driven B Cell metabolic dysregulation in chronic rhinosinusitis with nasal polyps: insights from Mendelian randomization and single-cell RNA sequencing - Wu, Jian; Sun, Yifang; Wang, Shuyue; Zhang, Qian; Lin, Ying; Liu, Caipeng; Ai, Maomao; Yu, Feng; Cao, Lei (Frontiers in Pharmacology, 2025)
BackgroundChronic rhinosinusitis with nasal polyps (CRSwNP), an inflammatory condition of unclear etiology, may involve immune dysregulation and metabolic alterations.MethodsUtilizing Mendelian randomization, we investigated causal links between CRSwNP and profiles of 731 immune cell types and 1,400 metabolites. Single-cell RNA sequencing (scRNA-seq) was employed for cell type identification and transcription factor analysis. Metabolic profiling characterized cellular subpopulations, while Gene Set Enrichment Analysis (GSEA) and machine learning pinpointed key genes functionally linked to immune and inflammatory pathways (categorized via WGCNA and Metascape).ResultsWe identified expression of HLA-DR on CD33− HLA-DR + B cells and the lipid metabolite 1-stearoyl-2-arachidonoyl as risk factors for CRSwNP. scRNA-seq further revealed these specific B cell subpopulations exhibit metabolic levels linked to immune responses. Bulk RNA analysis confirmed upregulation of genes CD27 and DERL3, while machine learning identified a signature of ten key genes showing positive correlation with B cell regulatory functions.ConclusionThis integrated study advances understanding of immune-metabolic crosstalk in CRSwNP pathogenesis, highlighting the role of metabolite-influenced B cell subsets in shaping the immune microenvironment, thereby suggesting novel therapeutic targets.